Treasures from grandma's attic eaudiobook - Richardson, Arleta (christianaudio, 2016)
Journey back to Grandma's childhood on a Michigan farm in the 1800s for heartwarming stories that inspire faith and godly character. Arleta Richardson's beloved series, Grandma's Attic, returns with Treasures from Grandma's Attic, the fourth in the refreshed classic collection for girls 8 to 12. This compilation of tales recounts humorous and poignant memories from Grandma Mabel's childhood on a Michigan farm in the late 1800s. Combining the warmth and spirit of Little House on the Prairie with a Christian focus, this book transports readers back to a simpler time to learn lessons surprisingly relevant in today's world. Richardson's wholesome stories have reached more than two million readers worldwide. Parents appreciate the godly values and character they promote. Children love the captivating storytelling that recounts childhood memories of mischief and joy. Ideal for home, school, or church libraries, or to give as a gift certain to be treasured.